Temporal variation in infection of male sardine (Sardinops sagax) by a coccidian testicular parasite (Eimeria sardinae) - Malongweni, Nwabisa (Department of Oceanography, 2017)
Temporal variability in infection of South African male sardines (Sardinops sagax) by a testicular coccidian parasite Eimeria sardinae was examined between putative western and southern stocks of this fish species. Samples were collected by commercial vessels from five localities; Gansbaai, St Helena Bay, Mosselbay, Port Alfred and Port Elizabeth (west and south coast) between 2012 and 2013. A total of 461 sardines were examined for the presence of Eimeria sardinae, including 185 males and 41 females from west coast and 180 males and 55 females from the south coast. Sardine females did not show any infection by the parasite. For males, prevalence of infection was 74.9% for the western stock and 76.5% for the southern stock. Mean infection intensity and standard error of the western stock was 6.7±0.7 and for the southern stock was 8.3±1.0. Parasite abundance and standard error of the western stock was 5.3±0.2 and 6.1±0.3 for the southern stock. A significant difference was observed within testes position (anterior, middle and posterior), with anterior being highly infected followed by middle and posterior (KW chi-square = 86.029, df = 2, p<0.05). Infection from the left and right testes did not show a significant difference (W= 623, p = 0.13). There was no significant difference in prevalence of infection, infection intensity index and abundance index per region across seasons. Seasonal pattern was the same in both stocks. There was a significant difference in monthly average GSI data of male sardines from west and south coast between 1996-2014 (KW = 5416.9, df = 11, p < 0.01). There was no significant difference between seasonal GSI and seasonal infection intensity index.